Briefing material for the First General Meeting between Representatives of the Caribbean Community (CARICOM) and the United Nations system (Division for the Advancement of Women New YorkUS, 1997)
Reports on states that have signed, ratified, acceded or succeeded to the Convention on the Eliminiation of All Forms of Discrimination Against Women (CEDAW). Notes declarations, reservations, objections and notifications of withdrawals of reservations relating to the CEDAW (only relevant member countries of the Caribbean Community). CARICOM provides information on women viz. education; legal changes ; and, public awareness of women's rights. List priorities and possible areas of collaboration.
DC